LC‐MS based metabolic and metabonomic studies of Panax ginseng. Issue 4 (19th February 2018) - Wu, Wei; Jiao, Chuanxi; Li, Hui; Ma, Yue; Jiao, Lili; Liu, Shuying
Abstract: Introduction: Panax ginseng has received much attention as a valuable health supplement with medicinal potential. Its chemical diversity and multiple pharmacological properties call for comprehensive methods to better understand the effects of ginseng and ginsenosides. Liquid chromatography‐mass spectrometry (LC‐MS) based metabonomic approaches just fit the purpose. Objective: Aims to give a review of recent progress on LC‐MS based pharmacokinetic, metabolic, and phytochemical metabolomic studies of ginseng, and metabonomic studies of ginseng intervention effects. Methods: The review has four sections: the first section discusses metabolic studies of ginsenosides based on LC‐MS, the second focuses on ginsenoside‐drug interactions and pharmacokinetic interaction between herb compounds based on LC‐MS, the third is phytochemical metabolomic studies of ginseng based on LC‐MS, and the fourth deals with metabonomic studies of ginseng intervention effects based on LC‐MS. Results: LC‐MS based metabonomic research on ginseng include analysis of single ginsenoside and total ginsenosides. The theory of multi‐components and multi‐targeted mechanisms helps to explain ginseng effects. Conclusion: LC‐MS based metabonomics is a promising way to comprehensively assess ginseng. It is valuable for quality control and mechanism studies of ginseng. Abstract : Liquid chromatography‐mass spectrometry (LCMS) based metabonomic approaches are comprehensive methods to better understand the effects of ginsenosides and ginseng. This work give a review of recent progress on LC‐MS based pharmacokinetic, metabolic, and phytochemical metabolomic studies of ginseng, and metabonomic studies of ginseng intervention effects. The theory of multi‐components and multi‐targeted mechanisms helps to explain ginseng effects. LC‐MS based metabonomics is a promising way to comprehensively assess ginseng. It is valuable for quality control and mechanism studies of ginseng.